2014
DOI: 10.1007/s10856-014-5155-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the polymeric niche on neural stem cell characteristics during primary culturing

Abstract: The polymeric niche encountered by cells during primary culturing can affect cell fate. However, most cell types are primarily propagated on polystyrene (PS). A cell type specific screening for optimal primary culture polymers particularly for regenerative approaches seems inevitable. The effect of physical and chemical properties of treated (corona, oxygen/nitrogen plasma) and untreated cyclic olefin polymer (COP), polymethymethacrylate (PMMA), PP, PLA, PS, PC on neuronal stem cell characteristics was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The pluripotent human embryonal carcinoma cell line NTera2/cl.d1 (NT2/D1) which is able to differentiate into mature neurons [53] was chosen as model to test this. NT2/D1 precursors are commonly used as a model for neurogenesis [40] and have already shown promise for implementation in experimental [5456] and clinical [57] cell replacement approaches. For a clearer presentation of our results we show a clear contrast between parallel (Figures 5(a1)–5(a5)) and perpendicular (Figures 5(b1)–5(b5)) water droplet behaviour and our observed NT2/D1 morphological changes (Figures 5(c1)–5(c5)) on nonstructured control and microstructured PMMA substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pluripotent human embryonal carcinoma cell line NTera2/cl.d1 (NT2/D1) which is able to differentiate into mature neurons [53] was chosen as model to test this. NT2/D1 precursors are commonly used as a model for neurogenesis [40] and have already shown promise for implementation in experimental [5456] and clinical [57] cell replacement approaches. For a clearer presentation of our results we show a clear contrast between parallel (Figures 5(a1)–5(a5)) and perpendicular (Figures 5(b1)–5(b5)) water droplet behaviour and our observed NT2/D1 morphological changes (Figures 5(c1)–5(c5)) on nonstructured control and microstructured PMMA substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(methyl methacrylate) (PMMA), also known by the trade name Plexiglas©, was selected as polymeric cell niche based on our previous work [40]. PMMA generally exhibits hydrophilic characteristics due to the ester groups in its macromolecular backbone (molecular formula: C 5 O 2 H 8 ) n ), is sufficiently and optically transparent to permit cell observation by microscopy, and exhibits good casting qualities for microstructuring [41].…”
Section: Methodsmentioning
confidence: 99%
“…Haubenwallner et al suggested that there is a direct connection of cell fate to the polymer niche [42]. In their study, they reveal that the use of a specific type of polymer with a tailored microenvironment can be considered as an effective tool for promoting essential cell characteristics for subsequent approaches and point out the necessity of using a cell type specific screening approach when referring to synthetic materials and material treatments for particular cell types.…”
Section: Introductionmentioning
confidence: 98%